China's Structural Change and the Impact on Korea's Industrial Growth - Sunghoon Chung (Korea Development Institute (KDI), 2016)
Until 2014, demand for durable goods was at the heart of China's domestic market growth. This, combined with the expansion of global value chains(GVC), contributed significantly to the rise of Korea's key industries, particularly that of heavy and chemical products, including electrical and electronic devices. Today, however, China faces two concurrent challenges, a slowdown in growth and a structural shift in domestic demand to services. As a result, a considerably large impact will likely be felt across the Korean heavy and chemical industries, the biggest beneficiaries of the rapid increase in China's domestic demand. Under the circumstances, Korea's policy makers and industrial entities need to enhance their understanding of the changes in the Chinese economy and develop preemptive countermeasures by reforming existing business structures. Additionally, researchers must provide more in-depth studies on China's evolving domestic market. - The rapid expansion in China's domestic market was led by the demand for durable goods until 2014. - China's durable goods-led growth in the domestic market combined with the expansion of GVCs has contributed significantly to the growth of the Korean economy. - Korea's heavy and chemical industries were the biggest beneficiaries. - However, China is currently faced with two concurrent challenges, slowdown in growth and changes in its industrial structure, which are also occurring in the domestic market. - In fact, the shift in China's domestic demand towards services is a natural phenomenon given its current economic structure and income level. - China's slow growth and the structural shift in domestic demand will deal a heavy blow to Korea's key industries, whose growth has been largely attributed to China's strong demand. - If the series of recent events in China are regarded as an integral part of the shift in the industrial structure, it would be possible to predict the direction of China's changes. - Korea's industries must be aware of the changes in the Chinese economy and develop countermeasures that include reforming business structures. - Simultaneously, more in-depth studies are needed on the changes in China's domestic market. ※ Written based on Chung, Sunghoon, "Global Value Chains and Impacts of China's Structural Changes," in Kyungsoo Choi (ed.), Structural Changes of the Chinese Economy and New Opportunities for Korea, Chapter 2, Research Monograph 2015-09, Korea Development Institute, 2015 (in Korean). (*The full text of Research Monograph will be released later on.)
Keywords: 330